Blindness in eclampsia: CT and MR imaging. Issue 7 (July 1989) - Duncan, R; Hadley, D; Bone, I; Symonds, E M; Worthington, B S; Rubin, P C
Abstract : Three cases of cortical blindness complicating eclampsia are described, with magnetic resonance imaging (MRI) and X-ray computed tomography (CT). The correspondence of MRI lesions (hyperintense on T2 weighted, and hypointense on T1 weighted sections) and low attenuation lesions on CT scan indicated ischaemia rather than haemorrhage as the pathological mechanism.